2021
DOI: 10.1177/00031224211007450
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Generosity: How the Norm of Generalized Reciprocity Bridges Collective Forms of Social Exchange

Abstract: This study examines the potential for small-scale acts of giving that are not directly reciprocated, or generalized generosities, to build social bonds and promote contributions to the group. Social exchange theorists define such acts as generalized exchange. The potential for generalized exchange to build strong social bonds relative to other forms of exchange is the subject of theoretical debate. In this article, I build on two prominent theories of social exchange—affect theory and the theory of reciprocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Existing studies have demonstrated that individuals' thriving at work, as an internal self-regulatory psychological state (Porath et al, 2012), could be the mechanism linking exchange relationship perception and outcomes at work (Xu et al, 2017;Chang and Busser, 2020). This finding is theoretically important because exchange relationship perception can affect an individuals' (Meier and Semmer, 2013;Quratulain et al, 2018;Whitham, 2021). Our findings suggests that the selfregulatory psychological consequences of how non-balanced reciprocity may have wide behavioral implications.…”
Section: Theoretical Contributionsmentioning
confidence: 53%
“…Existing studies have demonstrated that individuals' thriving at work, as an internal self-regulatory psychological state (Porath et al, 2012), could be the mechanism linking exchange relationship perception and outcomes at work (Xu et al, 2017;Chang and Busser, 2020). This finding is theoretically important because exchange relationship perception can affect an individuals' (Meier and Semmer, 2013;Quratulain et al, 2018;Whitham, 2021). Our findings suggests that the selfregulatory psychological consequences of how non-balanced reciprocity may have wide behavioral implications.…”
Section: Theoretical Contributionsmentioning
confidence: 53%
“…Public attitudes on trade should also reflect a second type of reciprocity that has received relatively less attention in the field of International Relations: “generalized reciprocity.” Generalized reciprocity exists when one agent’s behavior toward a second agent affects the latter’s willingness to cooperate with all actors. 3 In other words, whereas direct reciprocity implies that Player A’s actions towards Player B influence B’s actions towards A, generalized reciprocity implies that A’s behavior towards B will influence B’s behavior beyond their interactions with A. Laboratory-based experiments consistently show that cooperative and un-cooperative behavior spreads in this manner: subjects that are on the receiving end of a cooperative or generous (uncooperative or ungenerous) act in one interaction are more likely to behave in a cooperative or generous (uncooperative or ungenerous) manner towards unconnected third parties (Berkowitz & Daniels, 1964 ; Dufwenberg et al, 2001 ; Fowler & Christakis, 2010 ; Gray et al, 2014 ; Greiner & Levati, 2005 ; Simpson et al, 2018 ; Stanca, 2009 ; Whitham, 2021 ; Zitek et al, 2010 ).…”
Section: The Impact Of Foreign Protectionism On Public Support For Op...mentioning
confidence: 99%
“…In the context of trade policy, a foreign country’s trade barriers may generate feelings of resentment, causing individuals to feel that their country should also be entitled to raise import barriers themselves. Second, when individuals learn that one foreign country is protectionist, they may change their views about the strength of the global norm surrounding free trade (Stanca, 2009 , 192; Whitham, 2021 ). If someone believes that norms of cooperation and free trade are widely ignored, they are likely to conclude that their country should not abide by these conventions either (Goldstein, 1998 ).…”
Section: The Impact Of Foreign Protectionism On Public Support For Op...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another premise is that a person begins an encounter with the goal of maximizing profit at the lowest possible expense; the individual is motivated by, “What s in it for me?” A third assumption is that people analyze the profit and expense of doing something before doing it. Finally, the theory posits that people are aware that the pay-out will differ from one person to another, as well as from one person to another over time ( Whitham, 2021 ). Several researchers have found the engagement or disengagement of the workers due to social exchange of behaviors (knowledge-hiding behavior in this case) and concluded that certain behaviors could lead to disengagement and adversely impacted performance ( Yin, 2018 ).…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%